To Warn or Not to Warn: Management Disclosures in the Face of an Earnings Surprise - Kasznik, Ron; Lev, Baruch (The Accounting Review, 1995)
[We examined management's discretionary disclosures prior to a special, yet important, event-a large earnings surprise. In what ways do managers alert investors to the surprise, and what is investors' reaction to such warnings? To address these questions, we analyzed all managerial disclosures prior to the surprising earnings release. Less than ten percent of our large-surprise firms published quantitative earnings or sales forecasts, while 50 percent of the firms kept silent. Firms facing earnings disappointments were more likely to make a disclosure, and larger disappointments were preceded more often by "harder" (more quantitative and earnings-related) warnings. We found the likelihood of warnings to be positively associated with firm size, the existence of a previous forecast, and membership in a high technology industry. Finally, warnings tend to be issued for permanent earnings disappointments, while transitory disappointments are more likely to occur without prior warning.]